Inventory Control Analysis Using The Economic Order Quantity and Reorder Point Methods in Controlling Wheat Flour Raw Material Inventory at Ciki Bakery MSMEs - Putri, Nisa Felinia (Journal Of Accounting Management Business And International Research, 2022)
This study aims to determine the control of raw material inventory carried out by Ciki Bakery MSMEs and the comparison of the total cost of raw material inventory using the Ciki Bakery MSME policy with the Economic Order Quantity method. The data analysis method used in this study is qualitative with a descriptive approach. Data collection techniques with the method of literature study and direct observation. The results of the study found that the Economic Order Quantity method has optimal results compared to the method applied in MSMEs. This is evidenced by the frequency of bookings which have a considerable difference from 72 times to as many as 4 bookings during 1 year 2021. As well as less inventory costs, namely Rp. 291,000, the difference is Rp. 1,222,000 compared to the MSME method.